CAPILLARY WATER RISE IN PEAT SOIL AS AFFECTED BY VARIOUS GROUNDWATER LEVELS - Muhammad Imam Nugraha; Wahida Annisa; Lailan Syaufina; Syaiful Anwar (Indonesian Journal of Agricultural Science, 2016)
Capillary water in peatlands has a very important role in supplying water to the root zone of plants. The current water content in the root zone depends mainly on groundwater levels in some areas with shallow water levels. The study aimed to measure the capillary water dynamics in peat soils at various soil densities and groundwater levels which were observed from the changes in peat color, moisture distribution, water content and hydrophobicity of peat soil. The study was conducted in the greenhouse of Indonesian Swampland Agricultural Research Institute, Banjarbaru, South Kalimantan. The experiment was arranged in a randomized block design with two factors and three replications. The first factor was the bulk density (BD) of peat, namely BD-1 (on actual condition, 0.1 g cm-3) and BD-2 (compressed into 0.2 g cm-3). The second factor was simulated groundwater levels (GWL) consisting of GWL-1 (-100 cm), GWL-2 (-70 cm) and GWL-3 (-40 cm) from soil surfaces. The results showed that the rise of capillary water in peat soil reached a maximum height of 50 cm which was characterized by the increase in water content at the top layer in the range of 105–127% for BD-1 and 141–181% for BD-2. The highest value of water content (308%) was achieved in the treatment of GWL-3 with BD-2 and the lowest (37%) was in the treatment of GWL-1 with BD-1. The rate of capillary water rose progressively corresponded to the increase in BD value because the number of micropores of BD-2 was greater.